The effect of school´s ethnic composition on Mathematics results of students with immigrant origin in primary school - Seabra, T.; Carvalho, H.; Ávila, P. (Portuguese Journal of Social Science, 2019)
Scientific interest in the impact of the school composition effect on student performance has been reflected in the literature for several decades (since Coleman, 1966) and has recently intensified. In Portugal, sociological research in this field has been scarce, in particular research based on extensive methodologies. Taking 1st Cycle students and their Mathematics results as reference, the present study sought to contribute to this field. The objective was to identify the main effect and the moderating effect of school composition (socioeconomic and ethnic) on students' results, controlling the effect of individual and school variables, whose effects on school outcomes are already known, such as socioeconomic status (SES), gender, school trajectory, and school size. We particularly sought to understand whether school composition affects the students’ results, and whether the effects vary with students’ national origins. The research was supported by an extensive database containing information on 23,143 students at 522 public schools in the Lisbon Metropolitan Area. A multilevel analysis was developed, considering student and school levels. The dependent variable was the Mathematics results of fourth-grade students in the 2015 National Attainment Test. We concluded that the effect of school’s social composition is more important to student performance than that of school’s ethnic composition and also that the students from PALOPs (Portuguese-speaking African Countries) benefit more than any others when they attend schools with a higher average SES.